The role of fluoxetine on macrophage function in chronic pain (Experimental study in Balb/c mice) - Dwi Pudjonarko; Edi Dharmana; OS Hartanto (International Journal of Science and Engineering, 2015)
Chronic pain raises stress conditions such as depression that can lower the cellular immunity. Fluoxetine is an antidepressant  used as an adjuvant in pain management but no one has been linked it with the body immune system. The objectives of this research were to proof the benefits of fluoxetine in  preventing degradation of macrophage function in chronic pain by measuring the macrophage phagocytic index , macrophage NO levels and the liver bacterial count in BALB/c mice infected with Listeria Monocytogenes.A Post Test - Only Control Group Design was conducted using 28 male mice strain BALB /c, age 8-10 weeks. The control group (C), mice got the same standard feed as the other groups. Chronic pain group (P), mice were injected with 20μL intraplantar CFA on day-1. Pain + fluoxetine early group (PFE) were treated with P + fluoxetine 5 mg / kg ip day-1, the 4th, the 7th and the 10th, while the Pain + fluoxetine late group (PFL) were treated with P + fluoxetine 5 mg / kg ip on day 7th and 10th. All mice were injected with 104 live Listeria monocytogenes iv on day 8th. Termination was performed on day 13th. Differences within groups  were analyzed using  One-way ANOVA and Kruskall Wallis, whereas the correlation of variables were analyzed using  Pearson's product moment. The experimental results showed that The macrophage phagocytic index and NO macrophage level (pg/mL) in PFE group(2,24±1,013; 0,24±0,239) was higher than than P group (1,68±0,920; 0,21±0,263) and there was no different in the macrophage phagocytic index of PFE group compared to C group (p=0,583; p=0,805). In PFL group (4,32±1,459; 0,54±0,294) the macrophage phagocytic index as well as NO macrophage level (pg/mL) was higher than P group (1,68±0,920; 0,21±0,263) with p=0,002; p=0,017. P group Bacterial count (log cfu/gram) (2,30±0,849) was significantly higher than C group(1,15±0,223) (p=0,007), while PFE group bacterial count (1,96±0,653) and PFL group bacterial count (1,84±0,403) compared to C (1,15± 0,223) was not significantly different (p=0,093; p=0,220). Correlation found between macrophage phagocytic index and macrophage NO (r=0,515, p=0,005).Macrophage phagocytic index and macrophage NO showed no correlation with bacterial count (r=-0,051, p=0,798; r=-0,071, p=0,719).It can be concluded that fluoxetine significantly incerases macrophage phagocytosis index and macrophages NO level in mice with chronic pain,  on the other hand fluoxetine decreases liver bacterial count . There is a positive correlation between macrophage phagocytosis index and macrophages NO level, while no correlation observed  among two variables with mice liver bacterial count in chronic pain.